Perception of conventional TV and OTT video streaming platforms among university students in Klang Valley - Chan, Hern Xi (2023)
In the past 10 years, over-the-top (OTT) video streaming platforms have slowly emerged in the market, challenging the dominance of conventional TV. The improved viewing experience of the OTT platforms has changed the viewing behaviour of the audience and caused dissatisfaction towards conventional TV. Therefore, this study explores (1) the preference of conventional TV and (2) OTT platforms among university students in Klang Valley by using the seven components of uses and gratification approach and (3) the indulgence level towards conventional TV and OTT platforms. This study was conducted on 100 university students from Klang valley who have watched TV within the past year and are user of OTT video streaming platforms. The data is collected with a quantitative research method in the form of online survey questionnaire using google forms. Uses and gratification (U&G) theory and Technology Acceptance Model (TAM) are adopted in this study to explain the findings. The findings show that the respondents prefer OTT platforms over conventional TV in all seven components of U&G theory. However, the respondents had lower satisfaction with the information and financial benefit components on both conventional TV and OTT platforms.